STRATEGI PERTUMBUHAN KEKAYAAN DENGAN ALOKASI ASET INVESTASI dan PERENCANAAN PENSIUN, Studi pada High Net Worth Individual (Bapak Surya) - , Devananda Wira Prahasta ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is a study on High Net Worth Individuals where HNWIs then serve as the research object (Client). The main issues raised in this research is a strategy to increase the wealth and retirement planning, and to solve both increasing wealth and pension planning problems were used approach in wealth management. The client is Mr. Surya who has a wife and four children. Clients at this time invest more in assets that are less profitable, and therefore needed rebalancing of assets in order to find assets that have a high return with minimal risk at a time can be structured to the needs of retirement. Evaluation and analysis is based on family financial data and client risk tolerance. From these data it will be proposed two scenarios, or proposed investment is then described in the proforma balance sheet and cash flow.